Laser Application for Diseases of the Anorectal Region - S. A. Frolov; A. M. Kuzminov; D. V. Vyshegorodtsev; V. Yu. Korolik; T. A. Alibekova; I. A. Mukhin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to summarize the literature data of use of laser technologies in the treatment of anorectal diseases.   Key points. Lazer intervention technologies in the treatment of anorectal diseases such as haemorrhoids, anal fistula, anal fissure and pilonidal disease makes it possible to significantly reduce the intensity of pain syndrome, shorten the time of wound healing and also reduce the duration of the period of disability of the patient without worsening the quality of life. The main advantages of minimally invasive techniques are the absence of extensive wounds, minimal complications and reduction of the disease recurrence rate, minimally invasive methods are almost as effective as traditional ones. Besides, the use of laser allows to perform minimally invasive interventions under local anaesthesia in a day hospital.   Conclusion. It is necessary to further study and improve the use of laser technologies in the treatment of anorectal diseases, and to actively introduce techniques into practice to improve the results of treatment of patients with these nosologies.